NALAR SAINS DALAM MENYINGKAP TUHAN: KOMUNIKASI KRITIS DALAM MEMBANGUN NALAR KRITIS TENTANG TUHAN - Firman Firman (Fakultas Dakwah dan Komunikasi, 2015)
Confidence is still one important theme that is timeless and continues to be discussed as a very broad spectrum. Especially in establishing critical communication about the existence of God and relate it to the phenomena in the world of science. The origin of the belief in God seems to be from a business menjelaskan human experience of new things and events that are beyond the natural habits (eg natural disasters). God exists as a gap filler on matters excluded and abnormal in nature. Jevons mentions that God begins to attempt to explain the irregularities and accidental events. In the form of this shift, the Lord reconciled with science. The gaps being filled only strengthen the evidence of God, rather than get rid of it.